2020
DOI: 10.1149/1945-7111/aba5d5
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electrodeposition of Ultrathin Polyaniline Films and Mechanistic Understanding of their Anion-Mediated Electrochemical Behavior

Abstract: Electrode materials which undergo anion insertion are of interest for next-generation energy storage devices and electrochemical water desalination. Polyaniline (PANI) is a robust and well-studied electrode material for anion insertion, but to date we have been unable to establish the electrochemical and anion-binding performance of PANI at nanoscale thicknesses because these thicknesses are not obtainable using standard PANI deposition procedures. Here, we report a new pulsed electrodeposition procedure for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 92 publications
1
16
0
Order By: Relevance
“…For example, the CV data for an 83 nm thick Ani/ MoCl 5 film deposited via 300 oMLD cycles at 150 °C is shown in Figure 3 4 The Ani/oMLD film also does not exhibit sharp redox features at 0.13 V and 0.41 V vs Ag/AgCl, as would be expected for pAni at the pH of 3.5 employed in these experiments. 31,69 This suggests that the Ani/MoCl 5 oMLD process does not yield pAni films. This is surprising, as oMLD is thought to proceed via oxidation and quenching of surface monomers, which should be equally viable for Ani and Py.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the CV data for an 83 nm thick Ani/ MoCl 5 film deposited via 300 oMLD cycles at 150 °C is shown in Figure 3 4 The Ani/oMLD film also does not exhibit sharp redox features at 0.13 V and 0.41 V vs Ag/AgCl, as would be expected for pAni at the pH of 3.5 employed in these experiments. 31,69 This suggests that the Ani/MoCl 5 oMLD process does not yield pAni films. This is surprising, as oMLD is thought to proceed via oxidation and quenching of surface monomers, which should be equally viable for Ani and Py.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…29,30 This approach is not easily applied to 3D substrates. Synthesis of these polymers can also be achieved using electrodeposition, which provides some control over polymer film thickness, e.g., by pulse deposition, 31,32 but this approach suffers from similar challenges regarding molecular structure control, and electrodeposition onto porous substrates is challenging. 33,34 Over the last 30 years, research into vapor-phase polymerization (VPP) has established the groundwork to form conformal thin films of conjugated polymers with control over the molecular structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Films were deposited on the working electrode using a pulsed deposition technique established previously. 36,37 Here, 0.7 V vs SSC was applied for 1.5 s, followed immediately by a 1.5 s relaxation at 0.0 V vs SSC. 40,41 This cycle was repeated until an electrochemical quartz crystal microbalance (EQCM) frequency decrease was achieved corresponding to a desired film thickness (mass).…”
Section: Methodsmentioning
confidence: 99%
“…Quinton et al discovered that the redox and attachment properties of anions are dependent on the nanoscale thickness of PANI. It was found that the PANI films of thickness less than 10 nm have an excellent chloride ion uptake which is important for desalination application, and the PANI films with a thickness of approximately 100 nm have excellent capacity in SO 4 2– solutions because the proton donor/acceptor will be SO 4 2– /HSO 4 – in the PANI . Polyaniline-based compounds have been shown to be excellent electrode materials for chloride ion storage.…”
Section: Introductionmentioning
confidence: 99%